1966
DOI: 10.1126/science.153.3739.1008
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C-Induced Increase of Dermatan Sulfate in Cultured Hurler's Fibroblasts

Abstract: In fibroblasts taken from patients witli Hurler's syndromne and grown in cultlure, dermatan sulfate constituted a larger percentage of the total sulfated glycosaminoglycans than it did in cultured fibroblasts from unaffected individuals. Moreover, the addition of ascorbic acid (vitamnin C) to the culture medium markedly increased the concentration of dermatan sulfate in the Hurler's fibroblasts but not in the normal fibroblasts. The biochemical phenotype of the Hurler's cells persisted during 28 weeks of seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

1968
1968
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
1
12
1
Order By: Relevance
“…The data reported here extend and amplify preliminary studies from this laboratory which demonstrated that the classically accepted biochemical phenotype of Hurler syndrome, i.e., increased dermatan sulfate concentration within cells, persisted in fibroblast cultures derived from the skin of Hurler patients (10). Additional data have been obtained indicating that the biochemical defect is not limited to increased sulfated GAG synthesis but is also characterized by increased synthesis of nonsulfated GAG.…”
Section: The Journal Of Clinical Investigation Volume 47 1968supporting
confidence: 73%
“…The data reported here extend and amplify preliminary studies from this laboratory which demonstrated that the classically accepted biochemical phenotype of Hurler syndrome, i.e., increased dermatan sulfate concentration within cells, persisted in fibroblast cultures derived from the skin of Hurler patients (10). Additional data have been obtained indicating that the biochemical defect is not limited to increased sulfated GAG synthesis but is also characterized by increased synthesis of nonsulfated GAG.…”
Section: The Journal Of Clinical Investigation Volume 47 1968supporting
confidence: 73%
“…An increased accumulation of dermatan sulfate was found in the cell layer of Hurler syndrome fibroblasts when ascorbic acid was added to the culture medium (33). In scorbutic guinea pigs, cartilage cells were found to contain reduced levels of glycosaminoglycans, DNA, and glycogen.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that vitamin C increases the synthesis of glycosaminoglycans by skin fibroblasts (Schafer, Sullivan, Svejcar, Kofoed, and Robertson, 1966) whereas retinol reduces it (Danes and Beam, 1966b) offers a possible approach to therapy, though the basic defect is unlikely to be modified in this way.…”
Section: Resultsmentioning
confidence: 99%